PERLINDUNGAN HUKUM ATAS KARYA CIPTA DATA BASE - Nebula Ricisandhy, Yeanis; Supasti Darmawan, Ni Ketut; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 12, November 2013)
Legal protection of copyright works database that aims to determine whether the object database as one of the creatures, which uses the method of normative legal research, legal research is also called study normative legal doctrine, also referred to as library research or study documents, so it can be concluded that copyright protection database has been set in the Act - Act No. 19 of 2002 on Copyright in particular in article 12 of the letter I.
Keywords: Database, Copyright, Protection